2016
DOI: 10.1515/aopf-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of ethanolic extracts obtained from Ficus spp. leaves against the fish pathogen Aeromonas hydrophila

Abstract: The main goal of this study was to determine in vitro antimicrobial activity of ethanolic extracts obtained from the leaves of various Ficus species against Aeromonas hydrophila isolated locally from infected rainbow trout (Oncorhynchus mykiss Walbaum) with the aim of providing scientific rationale for the use of the plant in the treatment of bacterial infections induced by Aeromonas spp. in fish. Antimicrobial susceptibility testing was done on Muller-Hinton agar with the disc diffusion method. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…A. hydrophila revealed intermediate susceptibility concerning to ethanolic extract obtained from leaves of F. hispida (inhibition zone diameters were ranged from 8 to 12 mm). The most effective at least causing a zone of inhibition within 14-16 mm was an ethanolic extract from F. hispida leaves against P. fluorescens both in 200 µL of standardized inoculum of the bacterium (inhibition zone ranged from 15 to 16 mm in diameter) and 400 µL (14-15 mm) (Tkachenko et al, 2017d). Our results also indicated that extract obtained from F. mucuso offer a promising alternative to the use of antibiotics in controlling of infection caused by A. hydrophila, C. freundii, P. fluorescens, Y. ruckeri.…”
Section: Resultsmentioning
confidence: 99%
“…A. hydrophila revealed intermediate susceptibility concerning to ethanolic extract obtained from leaves of F. hispida (inhibition zone diameters were ranged from 8 to 12 mm). The most effective at least causing a zone of inhibition within 14-16 mm was an ethanolic extract from F. hispida leaves against P. fluorescens both in 200 µL of standardized inoculum of the bacterium (inhibition zone ranged from 15 to 16 mm in diameter) and 400 µL (14-15 mm) (Tkachenko et al, 2017d). Our results also indicated that extract obtained from F. mucuso offer a promising alternative to the use of antibiotics in controlling of infection caused by A. hydrophila, C. freundii, P. fluorescens, Y. ruckeri.…”
Section: Resultsmentioning
confidence: 99%
“…This study aimed to find a natural source, antimicrobial substance to replace antibiotics and chemotherapeutics for the treatment of Aeromonas-induced infections in fish aquaculture. According to our preliminary study and studies of other researchers [24,26,[28][29][30][31][32][33][34][35][36][37][38][39], it has been demonstrated that a number of ethanolic extracts derived from various Ficus species and their cultivars showed antibacterial activity against pathogenic isolates as well as antibiotic-resistant bacteria. The plant extracts of the above plant species can be used as a source which could yield alternative drugs to improve the treatment of infection caused by these Aeromonas strains.…”
Section: Methods Of Culturing Pathological Sample and Identification Mmentioning
confidence: 99%
“…A. hydrophila demonstrated the highest susceptibility to F. pumila. The highest antibacterial activity against A. hydrophila (200 µL of standardized inoculum) was displayed by F. benghalensis, F. benjamina, F. deltoidea, F. hispida, F. lyrata leaf extracts [39]. Among various species of Ficus genus exhibiting moderate activity against A. hydrophila (400 µL of standardized inoculum), the highest antibacterial activity was displayed by F. benghalensis, F. benjamina, F. deltoidea, F. hispida, F. lyrata leaf extracts [41].…”
mentioning
confidence: 99%
“…In our previous studies, the therapeutic potential for the use of various plants of Ficus genus in the control of bacterial diseases was evaluated against fish pathogens in in vitro study with promising results [33][34][35][36][37][38][39][40][41][42][43][44]. Most ethanolic extracts obtained from Ficus spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation